An Oral History of the Special Olympics in China Volume 2 : The Movement - Alford, William P.; Liao, Mei; Cui, Fengming; Alford, William P.; Liao, Mei; Cui, Fengming (Singapore Springer Nature, 2020)
This open access book contains the oral histories that were inspired by the work of the Special Olympics in conjunction with the 50th anniversary of its founding. The foreword and prefatory materials provide an overview of the Special Olympics and its growth in the People$1 (Bs Republic of China. The sections that follow record interview transcripts of individuals with intellectual disabilities living in Shanghai. In addition to chronicling the involvement of these individuals and their families in the Special Olympics movement, the interview transcripts also capture their daily lives and how they have navigated school and work.s
English
Keywords: Sociology; Social issues & processes; Economics; Oral history; Public health & preventive medicine; Politics & government; Disability Studies; Social Structure, Social Inequality; Sports Economics; Oral History; Public Health; Social Justice, Equality and Human Rights; Biotechnology; Social Structure; Human Rights; intellectual Disability; Special Olympics; Human Rights in China; Disability Rights; Open Access; Sociology; Social & ethical issues; Economics; Oral history; Public health & preventive medicine; Politics & government